The Role of Gender and Friends’ Gender on Peer Socialization of Adolescent Drinking: A Prospective Multilevel Social Network Analysis - Deutsch, Arielle R. (J Youth Adolesc, 2013)
Although socializing effects of friends’ drinking on adolescent drinking behavior have been firmly established in previous literature, study results on the importance of gender, as well as the specific role that gender may play in peer socialization, are very mixed. Given the increasing importance of gender in friendships (particularly opposite-sex friendships) during adolescence, it is necessary to better understand the nuanced roles that gender can play in peer socialization effects on alcohol use. In addition, previous studies focusing on the interplay between individual gender and friends’ gender have been largely dyadic; less is known about potential gendered effects of broader social networks. The current study sought to further investigate potential effects of gender on friends’ influence on adolescent drinking behavior with particular emphasis on the number of same-sex and opposite-sex friends within one’s friendship network, as well as closeness to these friends. Using Waves I and II of the saturated sample of the National Longitudinal Study of Adolescent Health (Add Health), adolescent friendship networks were used to calculate the mean drinking behaviors of adolescent friends. Multi-level models estimated the effects of individual drinking behaviors, friend drinking behaviors, and school-level drinking behaviors on adolescent drinking 1 year later, as well as moderating effects of gender composition of friendship groups and male and female friend closeness on the relationship between friends’ drinking behaviors and adolescent drinking behavior. Results documented that gender composition of friendship groups did not influence the effect of friends’ drinking on individual drinking 1 year later. However, closeness to friends did influence this relationship. As closeness to male friends decreased, the influence of their drinking behavior increased, for both boys and girls. A similar effect was found for female friends, but only for boys. Female friend closeness did not affect the relationship between peer alcohol socialization and girls’ alcohol use. The findings indicate that the role of gender on alcohol socialization may be more complex than previously thought, particularly when examining the potential role that alcohol use may play as a mechanism for social bonding within opposite-sex friendships and same-sex male friendships.